2014
DOI: 10.1093/her/cyt119
|View full text |Cite
|
Sign up to set email alerts
|

A social ecological approach to understanding correlates of lifetime sexual assault among sexual minority women in Toronto, Canada: results from a cross-sectional internet-based survey

Abstract: Stigma, discrimination and violence contribute to health disparities among sexual minorities. Lesbian, bisexual and queer (LBQ) women experience sexual violence at similar or higher rates than heterosexual women. Most research with LBQ women, however, has focused on measuring prevalence of sexual violence rather than its association with health outcomes, individual, social and structural factors. We conducted a cross-sectional online survey with LBQ women in Toronto, Canada. Multivariate logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 56 publications
3
23
0
6
Order By: Relevance
“…It calls attention to the connection between individual lives and the historical and socioeconomic context in which those lives unfold. Similarly, a social ecology conceptual framework incorporates multi-level domains associated with health among SMW [169]. It facilitates the examination of multi-level-structural, social, individual-factors associated with health outcomes that can guide the development of preventive strategies and health promotion interventions.…”
Section: Theoretical Limitationsmentioning
confidence: 99%
“…It calls attention to the connection between individual lives and the historical and socioeconomic context in which those lives unfold. Similarly, a social ecology conceptual framework incorporates multi-level domains associated with health among SMW [169]. It facilitates the examination of multi-level-structural, social, individual-factors associated with health outcomes that can guide the development of preventive strategies and health promotion interventions.…”
Section: Theoretical Limitationsmentioning
confidence: 99%
“…For example, this interrelatedness between minority stressors and experiences of violence was shown in a survey of lesbian and bisexual women by Balsam and Szymanski (2005), in which minority stress was associated with domestic violence victimization and perpetration, and in another study of lesbian women and gay men by Carvalho, Lewis, Derlega, Winstead, and Viggiano (2011), in which victims of interpersonal violence reported greater expectations of prejudice and discrimination. Additionally, a survey of lesbian, bisexual, and queer women in Toronto found that minority stressors were associated with experiences of sexual violence (Logie, Alaggia, & Rwigema, 2014). …”
mentioning
confidence: 99%
“…Nearly a quarter (24 per cent) of women in rural Peru, 28 per cent in Tanzania, 30 per cent in rural Bangladesh and 40 per cent in South Africa reported their first sexual experiences as not being consensual (Fontes & McCloskey 2011: 154). Logie, Alaggia and Rwigema (2014) found that LGBT+ survivors of sexual violence experience increased risks of post-traumatic stress disorder (PTSD), low self-esteem and self-rated health and low levels of social and familial support. Survivors and victims of GBV exhibit numerous negative health outcomes, including depression, sexually transmitted diseases, unwanted pregnancies, PTSD, self-harming behaviours, substance abuse, dissociation, eating disorders, sleep disorders and suicide (RAINN 2019; WHO 2017).…”
Section: Sexual Assault Harassment and School-related Gbvmentioning
confidence: 99%